EMPATI PEGAWAI DALAM PELAKSANAAN PELAYANAN PUBLIK DI KANTOR KELURAHAN BAHU - NADEAK, ROINTAN; PANGKEY, MASJE; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2019)
Based on the results of observations, the researchers saw that employee empathy in theimplementation of public services had improved. For indicators of empathy there is feeling, self awareness,role taking, and emotional. For this reason, the aim of this study is to find out employee Empathy inimplementing public services at the Bahu Village Office, Manado, North Sulawesi. The research methodused in this study is to use qualitative research methods that are descriptive in nature. The informants inthis study were 8 (eight) people, including 4 employees who worked in Bahu Village Office, 2 environmentalheads (ward heads 6 and ward heads 7) and 2 communities as service recipients. Data collection techniquesused are observation techniques, interview techniques and documentation techniques.Keywords: Empathy, Employees, and Public Services.